1997
DOI: 10.1093/ndt/12.6.1187
|View full text |Cite
|
Sign up to set email alerts
|

Relevance of conventional cardiovascular risk factors for the prediction of coronary artery disease in diabetic patients on renal replacement therapy

Abstract: Clinical symptoms as well as the cardiovascular risk profile are not valid predictors of CAD in diabetic patients with chronic renal failure. Therefore coronary angiography should be performed in all diabetic patients prior to renal transplantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0

Year Published

1997
1997
2019
2019

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(46 citation statements)
references
References 1 publication
1
45
0
Order By: Relevance
“…Braun et al (14) reported that 75% of diabetic dialysis patients with angiographically proven significant CAS had no symptoms. Koch et al (15) reported that only nine (26.3%) of 38 HD patients with CAS (Ͼ50% stenosis) had symptoms, and a CAG study performed by Pidgeon et al (16) on dialysis patients before renal transplantation showed that only 43% had symptoms. In contrast to these reports on occult CAS in CKD patients who were already on long-standing RRT, there have been few reports concerning the prevalence of CAS in patients with CKD just before the initiation of RRT.…”
Section: Discussionmentioning
confidence: 99%
“…Braun et al (14) reported that 75% of diabetic dialysis patients with angiographically proven significant CAS had no symptoms. Koch et al (15) reported that only nine (26.3%) of 38 HD patients with CAS (Ͼ50% stenosis) had symptoms, and a CAG study performed by Pidgeon et al (16) on dialysis patients before renal transplantation showed that only 43% had symptoms. In contrast to these reports on occult CAS in CKD patients who were already on long-standing RRT, there have been few reports concerning the prevalence of CAS in patients with CKD just before the initiation of RRT.…”
Section: Discussionmentioning
confidence: 99%
“…6 In fact, diagnosing CAD based only on classical symptoms and clinical factors in patients with CKD is extremely difficult .7 For example, the isolated analysis of the electrocardiogram (ECG) of HD patients has shown that the presence of a ST segment depression during sessions was efficient in diagnosing CAD in symptomatic patients. 8 That exam had sensitivity of 67% and specificity of 52% in patients undergoing renal replacement therapy.…”
Section: Assessment Of Atherosclerosis In Ckdmentioning
confidence: 99%
“…Therefore these results only reflect the potential for clinical symptoms to detect restenosis in symptomatic patients; they are not relevant to the primary detection of coronary artery disease where increased numbers of asymptomatic patients are to be expected because of the high prevalence of neuropathy. 26 The rate of angiographic restenosis is lower than that reported in previous studies (69% to 100%). [8][9][10] This is probably a result of selection bias, as in these studies only patients with clinical symptoms were re-evaluated angiographically.…”
Section: Procedural Variables In Coronary Angiography and Angioplastymentioning
confidence: 54%